2018
DOI: 10.1002/adem.201800302
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Foaming of Nickel, Monel, and Copper by the Reduction and Expansion of NiO and CuO Dispersions

Abstract: Nickel and its alloys are useful in a range of applications, and nickel foams have increased in popularity for functional applications, such as electrodes. Despite their versatility and interest for burgeoning technologies, there is only one well-developed method for producing porous nickel commercially. This work introduces a simple method for creating porosity in nickel and Monel (70% Ni, 30% Cu) that results in sub-micron to micron-scale pores and grains. This is accomplished by creating oxide dispersions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Developments in LMD and VPD have extended the range of np metals and alloys but with an attendant increase in complexity. Oxide reduction also allows for the production of alloys (e.g., [40,41] ), as long as the alloying elements are able to be reduced at temperatures where associated microstructural coarsening is not prohibitive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developments in LMD and VPD have extended the range of np metals and alloys but with an attendant increase in complexity. Oxide reduction also allows for the production of alloys (e.g., [40,41] ), as long as the alloying elements are able to be reduced at temperatures where associated microstructural coarsening is not prohibitive.…”
Section: Resultsmentioning
confidence: 99%
“…The strategy employs the vapor‐phase reduction of oxide particles dispersed within a metallic matrix. This process is a unique adaptation of the Additive Expansion by the Reduction of Oxides (AERO) method, which has been successfully implemented in Cu, [ 39 ] Ni, [ 40 ] Ag, [ 41 ] and alloys of them. The current embodiment is distinctly different from “traditional” AERO embodiments in that the oxide phase is the dominant component, requires lower processing temperature, and results in a bicontinuous nanoscale pore structure.…”
Section: Introductionmentioning
confidence: 99%
“…Because surface break-up is required, factors contributing to it will control the deposition rate. Microstructurally, the pure Ni-Cu alloy [24] and the 2% oxide [25] have been found to possess nanoscale and ultrafine grains after milling, but only the 2% oxide alloy retains them at the reaction temperature. Also, the 2% oxide alloy forms significant porosity, thereby enhancing available surface area for reaction and break-up.…”
Section: Resultsmentioning
confidence: 99%
“…If surface area or microstructural factors can be enhanced, it is expected that deposition can be accelerated. To that end, solid state foaming by oxide reduction has also been recently demonstrated to produce microscale and nanoscale porosity and ultrafine grain size in this alloy [25]. By combining the capability of MA to produce nanostructured functional alloys and fine dispersions of insoluble phases, we demonstrate that catalysis and solid state foaming may be united in an oxide-dispersed Ni-Cu alloy powder.…”
Section: Introductionmentioning
confidence: 88%
“…A few relevant studies have been reported. Atwater and coworkers synthesized Ni, Cu, and Monel (70% Ni, 30% Cu) foams with only low porosities (25–40%) using a method of intraparticle expansion by the reduction of CuO and NiO oxides . Eugenio et al fabricated nanostructured Ni–Cu foams using an electrodeposition process coupled with hydrogen bubble evolution as a dynamic template, resulting in somewhat uneven microstructure containing pure Ni, Ni–Cu solid solution, and Cu‐rich phases; additionally, they demonstrated the potential use of the Ni–Cu foams as a positive electrode for supercapacitor …”
Section: Introductionmentioning
confidence: 99%